The Influence of Digital Media on the Development of Critical Thinking Skills - Taruna Cakrabaskara; Ummu Hanifah; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2025)
Critical thinking is one of the essential 21st-century skills that must be fostered from the elementary school level. Amid rapid technological advancement, digital learning media has emerged as an alternative to create more interactive learning processes and to support cognitive skill development. This study aims to examine the influence of digital media on the development of elementary school students’ critical thinking skills through a literature review approach. The method employed is a meta-analysis of selected national and international journal articles published between 2020 and 2025. The search process was conducted via Google Scholar using the keywords “digital media,” “critical thinking,” and “interactive learning.” The findings indicate that digital media such as interactive e-modules, interactive videos, and project-based applications can enhance student engagement, support independent learning, and encourage reflection and evaluation processes, which are at the core of critical thinking. Furthermore, digital media also supports the implementation of the Kurikulum Merdeka and the strengthening of the Profil Pelajar Pancasila. The conclusion of this study highlights that digital media has a significant positive impact on students’ critical thinking skills, provided that its implementation is accompanied by adequate infrastructure readiness, teachers’ digital literacy, and appropriate learning strategies.